Peran Penting IMF Dalam Stabilisasi dan Pemulihan Ekonomi Global Di Tengah Krisis Keuangan Internasional - Fajri Asshidiqy; Widia Argita; Rihadatul Aisy; Rafli Rizki; Fitri Raya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the important role of the International Monetary Fund (IMF) in global economic stabilisation and recovery efforts, especially in the midst of the international financial crisis. The IMF serves as a critical provider of financial assistance to crisis-affected countries through an emergency lending mechanism, the IMF provides the financial support needed to address urgent economic pressures. In addition, the IMF acts as an economic policy advisor by providing guidance to its member countries. By designing appropriate structural reform programmes and economic policies, the IMF helps countries to recover from the crisis and build a stronger economic base. The importance of international co-operation is also a focus of the IMF in promoting global economic stability. This article has a formulation of the problem of how the IMF's role in providing emergency financial assistance for the economic stabilisation of countries affected by the international financial crisis. The analytical method used by the author is a qualitative approach. The results of the research in this journal are The IMF was established to maintain financial stability and world trade by providing loans to countries facing balance of payments crises that could threaten a country's economy.